Analysis of Influencing Factors on Participation Compliance, Slide Preparations Quality and Microscopic Reading Quality of Acid-Resistant Bacteria Slides at Ciamis Regency - Sriwardani, I Dewa Ayu; Dermawan, Asep; Kurniati, Iis; Feisal, Sonny (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: To find out the factors that influence participation compliance, slide preparations quality and microscopic reading quality in the External Quality Control program of Microscopic Cross Tests Acid Resistant Bacteria in Ciamis Regency in 2022-2023 Method: The research design is cross-sectional, population and total sampling of 27 respondents. Data analysis is Chi-Square with Fisher's Exact Test Result: Research data shows that the sig-p value of the period of employment variable for participation is 0.057, for the quality of slide preparations per quarter 0.695, 0.447, 0.550, 0.305, and the microscopic reading quality 0.036. The sig-p value of the training variable on participation is 0.226, on the quality of slide preparations per quarter 0.043, 0.388, 0.212, 0.219, and the microscopic reading quality 0.298. The sig-p value of the workload variable for participation is 0.204, for the quality of slide preparations per quarter 0.502, 0.091, 0.332, 0.502, and for the microscopic reading quality 0.050. The sig-p value of the microscope condition variable for participation is 0.005, for the quality of slide preparations per quarter 0.063, 0.106, 0.149, 0.323, and for the microscopic reading quality 0.036. The sig-p value of the incentive variable for participation is 0.001, for the quality of slide preparations per quarter 0.528, 0.302, 0.586, 0.189, for the microscopic reading quality of 0.013 Conclusion: there is a relationship between microscope conditions and incentive on participation compliance, there is a relationship between training on the slide preparations quality in the 4th quarter of 2022, there is a relationship between period of employment, workload, microscope conditions and incentive on microscopic reading quality